The Effect of Democratic Leadership Style on the Performance of Employees at PT. Medan Industry Area (Persero) - Andrysyah Andrysyah; Amin Basri; Junaida Junaida; Sudian Efendi; Nurhalimah Tambunan (Budapest International Research and Critics University, 2020)
The objective of this research were to determine the effect of democratic leadership style on performance of employees at PT. Medan Industry Area (Persero). The purpose of this research was to determine how the influence of democratic leadership style on performance of employees at PT. Medan Industry Area (Persero)